Jejak Manajemen Air di Masa Hindia-Belanda; Identifikasi Saluran Air di kawasan Stasiun Bogor: Trace of Water Management System in The Netherland-Indie Period: Identification of Water Channels in The Bogor Station Area - Hary Ganjar Budiman (JURNAL PANALUNGTIK, 2021)
This article describes the identification of the trace of the water management system during the Dutch East Indies era, in the form of a water channel found in the Bogor Station area. The analysis will be viewed from the spatial context; the significance of the water channel with the nearest river, the significance of the water channel to the nearest public facility, and its relevance to the racial urban space in Bogor. This research used a historical method that consists of four stages; heuristics, critics, interpretation, and historiography. Observations were made to explain the physical form and the estimated period of water channel construction. The results showed that the water channel near the Bogor Station was made with modern technology. In the past, the channel may have functioned as drainage that connected to the Ci Pakancilan. The location of the waters channel adjacent to public facilities and government administrative centers showed the accuracy of the Department of Public Works in anticipating floods and puddles in the area of European activity.